Optimalisasi Pengelolaan Aset IT melalui Sistem Manajemen Aset Berbasis Web - Saputra, Tio Aji; Ratnasari, Anita (TIN: Terapan Informatika Nusantara, 2025)
This research was conducted because the management of IT assets at PT. Putra Dumas Lestari was still carried out manually, making it prone to recording errors and inaccurate data. The purpose of this study is to develop a web-based asset management system that can optimize the recording, tracking, and reporting of company assets in a structured manner. This research was conducted at PT. Putra Dumas Lestari using the company’s IT asset data as the research object. The software development method used in this study is the Waterfall method, which consists of the stages of requirements analysis, system design, implementation, testing, and maintenance. The system was developed using the CodeIgniter 4 framework and a MySQL database, and is equipped with features for asset recording, stock addition, monitoring of asset outflow, real-time reporting, and automatic calculation of asset depreciation using the straight-line method. The results of system testing using the Black Box Testing method indicate that all main system functions operate properly and meet user requirements. With the implementation of this system, the company is expected to manage IT assets in a more structured manner, improve reporting accuracy, and support more effective asset-related decision-making.